PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI MELALUI KEPUASAN KERJA DAN KOMITMEN ORGANISASIONAL (Studi pada Pegawai Kesatuan Pemangkuan Hutan (KPH) Semarang Perum Perhutani Unit I Jawa Tengah) - Eko Suharyono, 11 52.02 0059 (Students Journal of Economic and Management, 2013)
The purpose of this study was to examine the influence of Transformational Leadership and Motivation on Performance mediated by Job Satisfaction and Organizational Commitment. The research methodology used was descriptive statistical method. In order to get the data, the researcher used questionnaires. The questionnaires were distributed to KPH Semarang, first unit Central Java, with the purposive sampling. After the data was analyzed, it is found that there is a negative relationship between Transformational Leadership and employee performance, without Job Satisfaction and organizational Commitment as a mediators. There is also found that there is a positive relationship between motivation and employee performance without Job Satisfaction and Organizational Commitment as mediators. Key words: Transformational Leadership, Motivation, Job Satisfaction, Organizational Commitment, Performance and Forest Stake holder